Loss of Expression of a Novel Chromatin Remodeler SMARCA1 in Soft Tissue Sarcoma - Patil, Pallavi A (J Cytol Histol, 2018)
INTRODUCTION: Vital cellular processes such as proliferation and differentiation are regulated by chromatin remodeling complexes. A variety of neoplasms have been discovered to have genomic alterations (GAs) and loss of immunohistochemical (IHC) expression of chromatin remodelers ARID1A (BAF250A), SMARCA2 (BRM), SMARCA4 (BRG1), and SMARCB1 (INI1). SMARCA1 (SNF2L) is another member of the chromatin remodelers, and has not yet been studied in neoplasia. As SMARCA1 is located on chromosome X, could be potentially inactivated by a single hit. We aimed to evaluate GAs and protein expression of SMARCA1 in soft tissue tumors. METHOD: The publically available cBioPortal.32e34 platform was queried to analyze data on soft tissue tumors from The Cancer Genome Atlas project (TCGA) related to SMARCA1 GAs. Our institutional archives were queried to collect 26 cases of soft tissue tumors including 10 undifferentiated sarcomas, 5 leiomyosarcomas, 6 liposarcomas, and 5 malignant peripheral sheath tumors (MPNST). IHC for SMARCA1 with an SNF 2C4 monoclonal antibody was performed on whole tissue sections. RESULTS: SMARCA1 GAs were present in 8/261 soft tissue sarcomas (3%) in the TCGA dataset. Leiomyosarcomas had most common SMARCA1 GAs in 6/99 cases. SMARCA1 deletions existed in 1/56 dedifferentiated liposarcomas and 1/48 undifferentiated sarcomas. No SMARCA1 GAs occurred in other sarcoma subtypes. SMARCA1 IHC was studied in the sarcoma subtypes with potential SMARCA1 alterations in our institutional cases. SMARCA1 nuclear expression was lost in 3/10 cases (30%) of undifferentiated sarcoma, and 2/5 cases of MPNST (40%). SMARCA1 expression was intact in all cases of leiomyosarcoma and liposarcoma. CONCLUSION: This is the first study to demonstrate loss of expression of SMARCA1 in soft tissue sarcomas subtypes, including undifferentiated sarcoma. Our study highlights merit for further investigation on the role of SMARCA1 in the differentiation process and molecular mechanisms of SMARCA1 inactivation.